This is an illogical statement: dangerous trends in anti-prison activism - Acey, Camille E. S. A. (Social justice, 2000)
Part of a special issue on critical resistance to the prison-industrial complex. The writer examines a number of problems that the “Schools Not Jails” (SNJ) movement, or variations thereof, pose to anti-prison activism. She notes that the SNJ became popular because of its straightforwardness and simplicity, and she argues that the movement could be dangerous because of such lucidity. Additionally, she discusses how attempts at popularizing a leftist political agenda often censure and cause difficulties for the project and prevent the development of a radical counter-hegemonic political discourse.